Integration of Gender Responsive Planning and Budgeting Programs - Aisyah Dewi; M. Arieliyanto; M. Asif Nur Fauzi (Pusat Studi Gender dan Anak (PSGA) Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Sultan Maulana Hasanuddin Banten, 2024)
Gender equality is the main focus in Indonesia's sustainable development agenda, especially in achieving the SDGs targets in 2030 and Golden Indonesia 2045. This development program emphasizes the importance of considering gender differences in formulating development policies and programs. In implementing gender sensitivity and response, gender needs analysis is an important stage in ensuring policies and programs are inclusive and responsive to community needs. The Gender Responsive Planning and Budgeting Program (PPRG) is the main instrument in integrating gender perspectives into development, with the aim of ensuring sustainable development that is fair and non-discriminatory for all individuals, regardless of gender. The research results show that integrating gender perspectives in policies and programs can increase development effectiveness, reduce gender inequality, and create a more inclusive and just social environment. By considering differences and needs between genders, including in the Gender-Based Development and Needs Analysis Program, Indonesia can ensure that every individual has equal and fair opportunities in various aspects of life. Integrating gender perspectives is not only a step towards achieving gender equality, but also a prerequisite for inclusive and sustainable development in the future. Through efforts like PPRG, Indonesia can ensure that development policies and programs reflect the needs and aspirations of all societal groups, thereby creating a more just, balanced and developed society as a whole.